Geochemistry of granitic aplite-pegmatite veins and sills and their minerals from the Sabugal area, central Portugal - Neiva, A.M.R. (2013)
Granitic beryl-columbite-phosphate subtype aplite-pegmatite veins and sills from the Sabugal area intruded a biotite > muscovite granite which is related to another two-mica granite. Variation diagrams of major and trace elements of whole rocks show fractionation trends. REE patterns and δ18O of whole rocks, BaO and P2O5 contents of K-feldspar, anorthite and P2O5 contents of plagioclase, major element and Li contents of muscovite and lithian muscovite support this series. Least squares analysis of major elements indicate that the biotite > muscovite granite and aplite-pegmatite veins and sills are derived from the earlier two-mica granite magma by fractional crystallization of quartz, plagioclase, K-feldspar, biotite and ilmenite. Modelling of trace elements shows that magmatic fl uxes and fl uids controlled the Rb, Sr and Ba contents of aplite-pegmatites, probably also lithium micas (zinnwaldite, polylithionite and rare lepidolite), cassiterite, columbite-tantalite, fl uorapatite and triplite. In aplite-pegmatites, lithian muscovite replaces primary muscovite and late lithium micas replace lithian muscovite. Complexely zoned columbite crystals are chemically characterized and attributed to disequilibrium conditions. Relations of granites and aplite-pegmatites and pegmatites from other Portuguese and Spanish areas are compared. The granitic aplite-pegmatites from Sabugal are moderately fractionated and the granitic complex type aplite-pegmatites from Gonçalo are the richest in Li and Sn, derived from a higher degree of fractional crystallization and fl uxes and fl uids control the Ba and Rb behaviours and Li, Sn, F and Ta concentrations.